(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Sustained release aceclofenac matrix tablets constituting Kollidon sustained release (KSR) (polyvinyl acetate and povidoneâ€based matrix retarding polymer) were developed in this study in an attempt to design a dosage form that manifests desirable release profile and thorough adherence to official monographs. Nine matrix tablet formulations were prepared by dry blending and direct compression method by varying the proportion of KSR and compression load with fixed percentage of aceclofenac. Among this, by comparing response variables of the prepared formulations with that of the marketed product, two formulations (KSR5 and KSR7) were chosen as the optimized formulations. The formulation showed close resemblance to commercial products and compliance with United States Pharmacopoeia USP specification.The exponential model was applied to characterize the drug release behavior from polymeric systems. It was found that nonâ€Fickian release is predominant in tablets containing KSR with a trend toward zeroâ€order kinetics.The study also involves in vivo evaluation of the optimized formulations to find out relevant pharmacokinetic parameters. Correlation of in vitro drug release with that of amount of drug absorbed in vivo has also been performed.